The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00104-020-01222-7
|View full text |Cite|
|
Sign up to set email alerts
|

Erhöhtes Risiko für tiefe Beinvenenthrombosen bei Intensivpatienten mit CoViD-19-Infektion? – Erste Daten

Abstract: Zusammenfassung Hintergrund Die Inzidenz tiefer Beinvenenthrombosen (TVT) bei intensivpflichtigen CoViD-19-Patienten wurde bisher nur in wenigen Studien untersucht. Prospektive vergleichende Studien mit Non-CoViD-19-Intensivpatienten fehlen gänzlich. Fragestellung Die Inzidenz TVT bei an CoViD-19 erkrankten Intensivpatienten verglichen mit Non-CoViD-19-Patienten, die im selben Zeitraum auf den Intensivstationen des Universitätsklinikums Augsburg behandelt wurden, wurden erhoben. Zudem soll untersucht werden, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
2
11
0
5
Order By: Relevance
“…32,33 Our findings are similar to prior studies reporting rates of thromboembolic events ranging from 18% to 69% in Covid-19 patients in ICU. 10,12,[15][16][17][18][19][21][22][23][24][25][26] Lower extremity DVT rates in ICU Covid-19 patients show wide variability with values as low as 2% or less to as high as 23% to 54% per multiple reports. 10,12,[15][16][17][18][19][22][23][24][25][26] Klok et al reported 49% cumulative incidence of thromboembolic complications, of which, only 3 were lower extremity DVTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Our findings are similar to prior studies reporting rates of thromboembolic events ranging from 18% to 69% in Covid-19 patients in ICU. 10,12,[15][16][17][18][19][21][22][23][24][25][26] Lower extremity DVT rates in ICU Covid-19 patients show wide variability with values as low as 2% or less to as high as 23% to 54% per multiple reports. 10,12,[15][16][17][18][19][22][23][24][25][26] Klok et al reported 49% cumulative incidence of thromboembolic complications, of which, only 3 were lower extremity DVTs.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Per published reports, the cumulative incidence of VTE (deep venous thrombosis and pulmonary embolism) in Covid-19 patients varies from 7.7% up to 69%. [10][11][12][16][17][18][19][20][21][22][23][24][25][26][27] The pathophysiology of CAC includes 2 mechanisms: systemic inflammation or cytokine storm causing endothelial cell activation and injury in the lung micro vasculature leading to pulmonary micro thrombosis and a hypercoagulable state leading to large vessel thrombosis. 3,8,28 Recent autopsy series of Covid-19 patients showed histologic pattern of diffuse alveolar damage, severe endothelial injury, widespread alveolar capillary thrombosis, micro angiopathy and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“… 26 The VTE group of COVID-19 patients was different from the non-VTE group in terms of D-dimer level, neutrophil-to-lymphocyte ratio (NLR), lymphocyte count, lactate dehydrogenase level, prothrombin time (PT), etc. 3 26 27 A significant increase in D-dimer is a sign of activation of coagulation and fibrinolysis, and is a good indicator for identifying high-risk populations with VTE, 28 which can be used as a highly sensitive test but with low specificity for detection of an active thrombotic process. 29 A study including 81 critically infected patients with COVID-19 concluded that D-dimer levels >1,500 ng/mL (normal range: 0.0–0.5 g/mL) had a sensitivity of 85.0%, a specificity of 88.5%, and a negative predictive value of 94.7% for detecting VTE events.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of COVID-19 in most studies required the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by real-time polymerase chain reaction (RT-PCR), but some were based on high clinical suspicion without the PCR results. In the clinical studies, 16 and 5 studies reported the incidences of outcomes only in the ICU (2,3,8,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) or non-ICU settings (27)(28)(29)(30)(31), respectively. Seven studies reported the incidence of outcomes in the ICU, and non-ICU settings.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%